PSYCHOLOGICAL FACTORS OF THE CREATIVITY MANIFESTATION OF MODERN MANAGERS - Poghosyan, Sona (Modern Psychology, 2023)
The psychological factors of creativity manifestation and their study results are shown in this article. The aim of this article is to show the psychological factors of the creativity of the modern manager and their correlation. The survey was conducted among 260 middle managers in the private and public sector. Questionnaire, testing and correlation extraction methods were used for the research. F. Williams creativity discovery methods (tests of divergent thinking and personal qualities), Cettel’s 16-factor questionnaire, Potemkin’s test of "social-psychological positions of a person in the motivational-demand sphere" were used. Among the managers, the average high level of creativity is combined with the average level of self-esteem, the striving for self-improvement and self-development, the freedom to express thoughts, the ability to develop and improve ideas, the spark of new ideas, the fear of making mistakes, ordinary thinking and giving in to the opinion of the majority are important contributing factors. We conclude that the manager’s creativity is determined by psychological factors and their unique correlation. We can state that the education and training of modern managers can receive new content, taking into account the importance of creativity as a systemic quality and the specifics of its manifestation.